2017
DOI: 10.1016/j.jdermsci.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in routine blood count might signal severe immune-related adverse events in melanoma patients treated with nivolumab

Abstract: Our results suggest that increased WBC count and decreased RLC are associated with G3/4 and lung/GI irAEs. Our analysis was based on the data point at which irAE occurrence was noticed and, therefore, these factors are not predictive, however, they could be a "signal" of severe irAE occurrence in patients with melanoma treated with nivolumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 32 publications
2
80
1
Order By: Relevance
“…These findings suggest the importance of predicting irAEs to avoid severe complications using simple methods. Indeed, Fujisawa et al [ 26 ] reported that the decrease of lymphocytes fraction could predict irAEs caused by nivolumab, but only in the very short period before irAE development. Since the interval for nivolumab administration is 2 or 3 weeks for melanoma patients, other prognostic biomarkers are needed for long intervals.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest the importance of predicting irAEs to avoid severe complications using simple methods. Indeed, Fujisawa et al [ 26 ] reported that the decrease of lymphocytes fraction could predict irAEs caused by nivolumab, but only in the very short period before irAE development. Since the interval for nivolumab administration is 2 or 3 weeks for melanoma patients, other prognostic biomarkers are needed for long intervals.…”
Section: Discussionmentioning
confidence: 99%
“…21 Additional hematologic markers of systemic inflammation include the PLR 17,18 19,20 A recent retrospective study of 101 patients with melanoma treated with nivolumab reported that an increased total white blood cell count and decreased lymphocyte count were associated with irAEs. 33 However, the ability of these tests to predict the occurrence of irAEs is unknown. In our study, baseline NLR, ALI, and PLR were not associated with an increased risk of irAE or pneumonitis.…”
Section: Dwight H Owen Et Almentioning
confidence: 99%
“…A recent study out of Japan has proposed the possibility of using routine blood counts as a biomarker of grade 3/4 or lung and gastrointestinal irAEs based on univariate and multivariate analysis of fluctuations in blood counts in melanoma patients receiving nivolumab. 95 This strategy may have merit as an etiology-independent, nonspecific sign of irAEs. However, the multicenter Japanese study focused on changes in blood counts that occurred during an event as compared to baseline measures before treatment.…”
Section: Etiology Of Iraes Revisitedmentioning
confidence: 99%